Role of microRNA-146a in normal and malignant hematopoietic stem cell function - Zhao, Jimmy L.; Starczynowski, Daniel T. (Frontiers in Genetics, 2014)
Regulation of hematopoiesis is controlled by microRNAs (miRNAs). In this review, we focus on miR-146a, and its role in regulating normal and malignant hematopoiesis. miR-146a is a negative regulator of immune cell activation by repressing two targets, TRAF6 and IRAK1. Genetic deletion of miR-146a confirmed a role of miR-146a during innate immune signaling as well as for hematopoietic stem cell (HSC) function. miR-146a is also implicated in the pathogenesis of human myelodysplastic syndromes (MDS) as it is located within a commonly deleted region on chromosome 5, and miR-146a-deficient mice exhibit features of an MDS-like disease. With new insight into miR-146a through genetic and expression analyses, we highlight and discuss the recent advances in the understanding of miR-146a in physiological hematopoiesis during steady state and inflammation, as well as in MDS.